KORELASI ANTARA WANITA, PERHIASAN, ‎DAN AURAT DALAM AL-QURAN SURAH AN-‎NUR AYAT 31 MENURUT PRESPEKTIF ‎MUFASSIR NUSANTARA - Jannah, Miftahul; Is, Fadhilah; Yuzaidi, Yuzaidi (Jurnal Ushuluddin, 2022)
In Islamic teachings, the relationship between jewelry and aurat has a significant impact on women. Even things that are attached to a woman, whether visible or hidden, are considered jewelry, and it is her duty to guard them. If these are deliberately exposed to non-mahram individuals, it is the same as revealing one's aurat. Through Q.S. an-Nur verse 31, the correlation between women, jewelry, and aurat will be clarified, as well as an analysis of the views of Nusantara mufassir (interpreters). The results of this study, based on Q.S. an-Nur verse 31, according to Buya Hamka, Hasbi Ash-Shiddiqiey, and M. Quraish Shihab, and the author's opinion regarding the correlation between women, jewelry, and aurat, suggest that the connection between these topics lies in the jewelry worn by women. Jewelry is divided into visible and hidden categories. Jewelry that is commonly visible is not considered aurat as long as it is not excessive, since women are naturally drawn to beauty and admiration. However, if jewelry that is meant to remain hidden is intentionally displayed, it becomes an exposure of aurat. According to the mufassir’s definition of aurat, it refers to parts of the body that must be covered to prevent provoking desire.